MORPHOLOGICAL VARIATION OF EARLY DAYS TO FLOWERING ON LOCAL RICE ACCESSIONS COLLECTED FROM PONOROGO - Niken Trisnaningrum; Alfu Laila (Universitas Gadjah Mada, 2017)
Local rice germplasm may play an important role in improving rice quality. One of the important to improve rice cultivar trait is days to flowering. Ponorogo is one of district of center rice production area where the farmers cultivate local rice varieties which is early days to flowering or short vegetative phase. Exploration of local early days to flowering rice accessions in Ponorogo resulted in 9 accessions. Flowering times ranged 51 to 91 days after sowing. Based on morphological variation, there were variation of plant height, number of leaves, number of tiller, number of panicle, number of grains per panicle, flowering time, grain size and weight of 100 grains. Morphological dendrogram made possible to identify three groups at similarity 0.88.